Effect of olive oil phenolic compounds on the aroma release and persistence from O/W emulsion analysed in vivo by APCI-MS. (December 2019) - Genovese, Alessandro; Caporaso, Nicola; di Bari, Vincenzo; Yang, Ni; Fisk, Ian
Abstract: The effect of the presence of virgin olive oil (VOO) phenolic compounds was studied during the in-vivo consumption of an olive oil-in-water (O/W) food emulsion, assessed by APCI-MS. VOO phenolic compounds were present at 593 mg kg −1 . Four volatile compounds, i.e. ethyl acetate, hexanal, hexanol and linalool, were monitored based on their physicochemical characteristics and their aroma impact. Olive O/W emulsions were stabilized by whey protein isolate (WPI) and xanthan gum. Our results suggested that ethyl acetate and hexanal have a "salting out" effect in the presence of VOO phenolics at swallowing of emulsion. Among the volatiles investigated, hexanal showed the highest release. The persistence in the breath was higher for linalool only, potentially due to its higher hydrophobicity. This study could be beneficial in the formulation of new functional foods to enhance aroma release and persistence in the presence of natural phenolic compounds. Graphical abstract: Unlabelled Image Highlights: O/W emulsions were formulated with olive oil phenolics, WPI and xanthan gum. Phenolic compounds exhibit a significant effect on the in-vivo aroma release. This effect was verified both for the intensity and the length of aroma release. Hydrophilic compounds had a higher initial intensity of release. Hydrophobic compounds had a longer persistence in the presence of VOO phenolics.